2003
DOI: 10.1039/b307050f
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenate, oxyalkyl and alkoxycarbonyl thermochemistry and rates for hydrogen abstraction from oxygenates

Abstract: Ab initio molecular orbital theory calculations are performed at the complete basis set (CBS-Q) level to determine thermochemical parameters (D f H 298 , S 298 , C T p ) of alcohols, methyl ethers, formates, acetates, hydroperoxides, methyl alkylperoxides and the corresponding methoxy, primary and secondary alkoxy radicals derived from these molecular families. A consistent set of 12 Benson groups transferable among these six molecular families is derived from CBS-Q results via regression together with 20 hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 80 publications
(123 reference statements)
3
76
1
Order By: Relevance
“…We have made two more signiÞcant and a number of relatively minor modiÞcations from the adopted pathway of Fisher et al; the thermochemistry of species involved in the low-temperature MF submechanism has been reestimated so as to be consistent with those of the high-temperature MF mechanism, i.e., we incorporate the work of Sumanthi and Green [35].…”
Section: Thermochemistry Experimental Values Formentioning
confidence: 97%
“…We have made two more signiÞcant and a number of relatively minor modiÞcations from the adopted pathway of Fisher et al; the thermochemistry of species involved in the low-temperature MF submechanism has been reestimated so as to be consistent with those of the high-temperature MF mechanism, i.e., we incorporate the work of Sumanthi and Green [35].…”
Section: Thermochemistry Experimental Values Formentioning
confidence: 97%
“…The isodesmic reactions used to determine the enthalpy of CH 3 CH 2 OOCH 3 are listed in Table 3, and our recommended value is -39 kcal mol -1 ; the values estimated with group additivity (-39.3) are also in good agreement. A value of -37.0 kcal mol -1 is reported in ref 25. CH 3 OOCH 3 was also calculated with isodesmic reactions (see Table 3).…”
Section: Geometries and Vibration Frequenciesmentioning
confidence: 99%
“…Methyl hydroperoxide, CH 3 OOH, has been the subject of numerous publications [20][21][22][23][24] since a comprehensive review by Dorofeeva et al in 2001. 25 They concluded that ∆H f (298.15K) ) -139.0 ( 5.0 kJ mol -1 represented the best estimate from values which ranged from -122 to -143 kJ mol -1 .…”
Section: Alkyl Hydroperoxidesmentioning
confidence: 99%